2018
DOI: 10.1371/journal.pone.0205601
|View full text |Cite
|
Sign up to set email alerts
|

Model of care and risk factors for poor outcomes in patients on multi-drug resistant tuberculosis treatment at two facilities in eSwatini (formerly Swaziland), 2011–2013

Abstract: IntroductionSince 2011 Médecins sans Frontières together with the eSwatini Ministry of Health have been managing patients with multi-drug resistant tuberculosis (MDR-TB) at Matsapha and Mankayane in Manzini region. This analysis describes the model of care and outcomes of patients receiving a 20 months MDR-TB treatment regimen between 2011 and 2013.MethodWe conducted a retrospective observational cohort study of MDR-TB patients enrolled for treatment between May 2011 and December 2013. An extensive package of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
(22 reference statements)
0
12
1
8
Order By: Relevance
“…[23,24] It is likely that such ART-naïve HIV co-infected patients were presenting with severe immunosuppression and hence denied the well-known benefits of life-saving ART in restoring their immune function. [21,22] Thus, the finding highlights the importance of ART in limiting the unfavourable treatment outcomes among MDR/RR-TB patients in high HIV burden countries.…”
Section: Plos Onementioning
confidence: 84%
See 1 more Smart Citation
“…[23,24] It is likely that such ART-naïve HIV co-infected patients were presenting with severe immunosuppression and hence denied the well-known benefits of life-saving ART in restoring their immune function. [21,22] Thus, the finding highlights the importance of ART in limiting the unfavourable treatment outcomes among MDR/RR-TB patients in high HIV burden countries.…”
Section: Plos Onementioning
confidence: 84%
“…In contrast, better treatment success rates of around 75% have been observed in similar cohorts in Botswana and eSwatini with similar high HIV and MDR/RR-TB co-infection MDR/RR-TB cohorts. [21,22] However, the patient in Botswana and eSwatini had received social support in the form of monetary incentives or nutritional and transportation support including psychological support at health facilities. No such social and psychological support mechanisms were made available in the current study setting and should be considered in the future for improving treatment outcomes.…”
Section: Plos Onementioning
confidence: 99%
“…Solely clinic‐based care approaches would probably have left behind patients from remote locations. Other community‐based care models used nurses living near patients’ homes or nurse‐led mobile injection teams for daily home visits, DOT and treatment provision . In our setting, patients received a monthly supply of oral and injectable drugs, and CTS ensured daily treatment provision, requiring fewer supervisory visits by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, many risk factors for unfavourable treatment outcomes of RR/MDR-TB patients have been identified [6]. These include HIV co-infection, diabetes mellitus, poor treatment adherence, delay in TB treatment initiation and history of previous TB treatment [6][7][8][9][10][11][12][13][14][15][16][17]. Evidence from Armenia on this topic is limited: previous studies have reported socio-economic factors such as education, income and occupation, and adverse drug events as the key factors for poor outcomes among MDR-TB patients [9,18,19].…”
mentioning
confidence: 99%